2020
DOI: 10.2147/dddt.s253293
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knockdown of hsa_circ_0059955 Induces Apoptosis and Cell Cycle Arrest in Nucleus Pulposus Cells via Inhibiting <em>Itchy E3 Ubiquitin Protein Ligase</em></p>

Abstract: Background: Circular RNAs (circRNAs) play an important role in the progression of intervertebral disc (IVD) degeneration (IVDD). Using bioinformatics analysis, we have found that the expression of circRNA hsa_circ_0059955 was significantly downregulated in IVDD tissues. However, the relevant mechanism of hsa_circ_0059955 in the progression of IVDD remains unclear. Methods: CCK-8 and flow cytometry assays were used to evaluate cell proliferation and apoptosis. In addition, Western blot assay was used to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Like circITCH, circ_0059955 is another circRNA transcribed from the host gene ITCH (Itchy E3 ubiquitin protein ligase). Kong et al (2020) demonstrated that circ_0059955 was significantly downregulated in IDD samples. Knockdown of circ_0059955 suppressed ITCH expression and inhibited proliferation, induced cell cycle arrest and promoted apoptosis of NP cells.…”
Section: Circ_0059955mentioning
confidence: 99%
“…Like circITCH, circ_0059955 is another circRNA transcribed from the host gene ITCH (Itchy E3 ubiquitin protein ligase). Kong et al (2020) demonstrated that circ_0059955 was significantly downregulated in IDD samples. Knockdown of circ_0059955 suppressed ITCH expression and inhibited proliferation, induced cell cycle arrest and promoted apoptosis of NP cells.…”
Section: Circ_0059955mentioning
confidence: 99%
“…Numerous studies have demonstrated that ncRNAs have critical functions in modulating IVD development (as discussed in recently published review articles [ 115 , 125 ]). Besides, some ncRNAs, including miR-15a-5p [ 126 ], miR-19b-3p [ 127 ], miR-25 [ 128 ], miR-26a-5p [ 129 ], miR-105-5p [ 130 ], miR-130b [ 131 ], miR-145-5p [ 132 ], miR-195 [ 133 ], miR-345-3p [ 134 ], miR-495-3p [ 135 ], miR-499a-5p [ 136 ], miR-502 [ 137 ], miR-660 [ 138 ], miR-2355-5p [ 139 ], miR-4478 [ 140 ], circKIF18A [ 141 ], hsa_circ_0083756 [ 142 ], hsa_circ_0059955 [ 143 ], circSPG21 [ 144 ], circPKNOX1 [ 145 ], circ-FAM169A [ 146 ], circERCC2 [ 147 ], circ-4099 [ 148 ], lncRNA XIST [ 149 ], and LncRNA NR2F1-AS1 [ 132 ] are revealed to be differently expressed in NP tissues and cells from IVDD patients. However, the investigation into the different mechanisms of IVDD in genetic animal models is extremely limited.…”
Section: Ncrnas In Intervertebral Disk Degenerationmentioning
confidence: 99%
“…Gene knockout and microbial co-culture are newer methods for NPC degeneration models. Kong et al [91] constructed a degenerative cell model by down-regulating the hsa_circ_0059955 gene of normal mouse NPCs and inducing NPC apoptosis and cell cycle arrest. In 2020, He et al [92] found that Cutibacterium acnes induce NPC degeneration by activating the NOD-like receptor thermal protein domain associated protein 3(NLRP3(-dependent pathway.…”
Section: Nucleus Pulposus Cell Degeneration Model Established By Biol...mentioning
confidence: 99%